Regulatory Thresholds as Disciplinary Signals: Evidence from Bank Nonperforming Loan Supervision - Thi Lan Nhi Phung; Chi Dat Le; Van Kien Pham (Ital Publication, 2026)
Persistent high levels of nonperforming loans (NPLs) remain a key threat to banking stability, yet limited evidence exists on how regulatory thresholds influence bank discipline and risk behavior. This study investigates whether supervisory NPL ceilings serve as effective disciplinary mechanisms that balance profitability and credit risk in commercial banking systems. Using a balanced panel dataset from multiple emerging-market banks between 2013 and 2023, we employ Hansen’s (1999) panel threshold regression to identify critical points at which bank behavior changes significantly. The findings indicate that when NPL ratios exceed an optimal threshold, banks exhibit heightened self-discipline by tightening credit growth and accepting lower short-term returns, demonstrating a strong regulatory disciplining effect rather than moral hazard. Conversely, when NPLs remain below the threshold, the traditional risk–return trade-off weakens, suggesting stability and prudence. The results highlight the importance of threshold-based supervision as a prudential instrument that enhances banking stability through behavioral signaling. The study contributes to signaling theory by conceptualizing regulatory thresholds as negative signals that trigger pre-emptive risk management and to policy design by offering empirical insights into optimizing supervisory frameworks.